THE EFFECT OF USING PICTURE WORD INDUCTIVE MODEL (PWIM) IN TEACHING WRITING DESCRIPTIVE TEXT AT ELEVENTH GRADE STUDENTS OF SMA NEGERI 4 PEMATANGSIANTAR - Elisa Sri Rejeki Girsang; David Togi Hutahaean; Melda Veby Ristella Munthe (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to determine the effect of using the Picture Word Inductive Model (PWIM) on students’ ability to write descriptive texts at SMA Negeri 4 Pematangsiantar. The research employed a quantitative method using a pre-test and post-test design with control and experimental groups. Two classes were selected through simple random sampling: XI-1 as the control group and XI-2 as the experimental group. The experimental group was taught using PWIM, while the control group was taught conventionally. The results showed that the experimental group’s mean score improved from 62.2 to 85.57, while the control group’s score increased from 63.08 to 71.63. The t-test result (3.43) was higher than the t-table value (2.382) at the 0.05 significance level, indicating a significant difference between the two groups. Therefore, it can be concluded that PWIM effectively improves students’ writing ability in descriptive texts.